2020
DOI: 10.3389/fimmu.2020.01008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NK-92 Cytotoxicity by CRISPR Genome Engineering Using Cas9 Ribonucleoproteins

Abstract: Natural killer (NK) cells are an attractive cell-type for adoptive immunotherapy, but challenges in preparation of therapeutic primary NK cells restrict patient accessibility to NK cell immunotherapy. NK-92 is a well-characterized human NK cell line that has demonstrated promising anti-cancer activities in clinical trials. Unlimited proliferation of NK-92 cells provides a consistent supply of cells for the administration and development of NK cell immunotherapy. However, the clinical efficacy of NK-92 cells ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 37 publications
1
67
0
Order By: Relevance
“… [72] In NK cells, CRISPR/Cas9 system could be used to augment NK cell anti-tumour functions by targeted CAR insertion and stably knock-outing or integrating genes of interest involved in NK cell exhaustion, activation, tolerance, or memory. [73] …”
Section: Generation Of Car-nk Cellsmentioning
confidence: 99%
“… [72] In NK cells, CRISPR/Cas9 system could be used to augment NK cell anti-tumour functions by targeted CAR insertion and stably knock-outing or integrating genes of interest involved in NK cell exhaustion, activation, tolerance, or memory. [73] …”
Section: Generation Of Car-nk Cellsmentioning
confidence: 99%
“…This resulted in superior CAR T cells with uniform CAR expression, reduced tonic signalling, reduced T‐cell exhaustion and improved anti‐tumor efficacy in a humanised murine tumor model 119 . Although high efficiency CRISPR‐HDR has remained difficult in primary NK cells, 120 a recent study has demonstrated a number of optimised genetic engineering approaches in NK‐92 cells 121 . NK‐92 cells were edited to have multiple gene knockouts of inhibitory receptors, knock‐in of a fluorescent protein, and insertion of constitutive promoters to reactivate endogenous CD16 and DNAM‐1 expression.…”
Section: Strategies To Enhance Endogenous Nk Cell Function In the Tmementioning
confidence: 99%
“…NK‐92 cells were edited to have multiple gene knockouts of inhibitory receptors, knock‐in of a fluorescent protein, and insertion of constitutive promoters to reactivate endogenous CD16 and DNAM‐1 expression. CRISPR‐engineered NK‐92 cells demonstrated strikingly enhanced cytotoxicity and could even mediate ADCC against previously hard to kill cancer cell lines 121 . Employing these methods in primary human NK cells could significantly improve adoptive NK cell therapy (Figure 5).…”
Section: Strategies To Enhance Endogenous Nk Cell Function In the Tmementioning
confidence: 99%
“…Although CRISPR/Cas9 can be delivered by both viral and non-viral systems, non-viral delivery of a ribonuclear protein (RNP) complex made up by the Cas9 nuclease and the single guide RNA (sgRNA) is preferred, since it limits off-target effects due to viral DNA integration. However, ex vivo non-viral delivery requires optimization, as efficiency is often very limited and viability a concern ( 61 ). Of note, CRISPR/Cas9 can be used to efficiently screen effective synthetic constructs electroporated into T cells ( 66 ), significantly speeding up the discovery of constructs for reprogramming adoptive NK cell functionality and specificity.…”
Section: Nk Cell Genetic Modification For Sustained Functionality In mentioning
confidence: 99%